A world of curiosities : a novel [compact disc, unabridged] - Penny, Louise (Penny, Louise. Three Pines mystery., 2022)
It's spring and Three Pines is reemerging after the harsh winter. As the villagers prepare for a special celebration, Armand Gamache and Jean-Guy Beauvoir find themselves increasingly worried. A young man and woman have reappeared in the Sûreté du Québec investigators' lives after many years. The two were young children when their troubled mother was murdered, leaving them damaged, shattered. Gamache and Beauvoir's memories of that tragic case, the one that first brought them together, come rushing back. Did their mother's murder hurt them beyond repair? As Chief Inspector Gamache works to uncover answers, his alarm grows when a letter written by a long dead stone mason is discovered. In it the man describes his terror when bricking up an attic room somewhere in the village. Every word of the 150-year-old letter is filled with dread. When the room is found, the villagers decide to open it up. As the bricks are removed, Gamache, Beauvoir and the villagers discover a world of curiosities. But the head of homicide soon realizes there's more in that room than meets the eye.